2020
DOI: 10.1096/fj.201901739rr
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial fragmentation in polycystic kidney disease acts as a modifier of disease progression

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a common monogenic disorder, characterized by bilateral renal cyst formation. Multiple pathways are de‐regulated in cystic epithelia offering good opportunities for therapy. Others and we have previously reported that metabolic reprogramming, including alterations of the TCA cycle, are prominent features of ADPKD. Several lines of evidence suggest that mitochondrial impairment might be responsible for the metabolic alterations. Here, we performed morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 34 publications
4
31
0
Order By: Relevance
“…Mdivi-1 also has been tested in CKD models; however, Mdivi-1 treatment seems to exhibit divergent functions in different studies. In Ksp-Cre;Pkd1 flox/- mice, administration of Mdivi-1 significantly reduced kidney/body weight, cyst formation, and improved renal function by interfering with Drp1 and rescuing mitochondrial fragmentation [ 101 ]. In UUO model, treatment with Mdivi-1 decreased mitochondrial PTEN-induced putative kinase 1 (PINK1), parkin RBR E3 ubiquitin protein ligase (PARK2), and LC3II levels; increased mtROS production; and worsened renal fibrosis following UUO [ 102 ], which suggested that Drp1-regulated PARK2-dependent mitophagy plays a protective role in kidney following injury.…”
Section: Mitochondrial Targeting For Aki and Ckd Therapymentioning
confidence: 99%
“…Mdivi-1 also has been tested in CKD models; however, Mdivi-1 treatment seems to exhibit divergent functions in different studies. In Ksp-Cre;Pkd1 flox/- mice, administration of Mdivi-1 significantly reduced kidney/body weight, cyst formation, and improved renal function by interfering with Drp1 and rescuing mitochondrial fragmentation [ 101 ]. In UUO model, treatment with Mdivi-1 decreased mitochondrial PTEN-induced putative kinase 1 (PINK1), parkin RBR E3 ubiquitin protein ligase (PARK2), and LC3II levels; increased mtROS production; and worsened renal fibrosis following UUO [ 102 ], which suggested that Drp1-regulated PARK2-dependent mitophagy plays a protective role in kidney following injury.…”
Section: Mitochondrial Targeting For Aki and Ckd Therapymentioning
confidence: 99%
“…Evidence suggests that the cystic epithelial lining shares neoplastic features (Rowe et al, 2013). Impaired mitochondrial structure and function play a role in ADPKD disease progression (Cassina et al, 2020). Metabolic reprogramming in PKD is similar to that reported in cancer (Rowe et al, 2013).…”
Section: Metabolic and Mitochondrial Reprogramming In Polycystic Kidnmentioning
confidence: 70%
“…Given the therapeutic potential of this approach, we have sought to determine the mechanisms responsible for producing the altered cellular metabolic state. A number of recent studies have focused on the mitochondrion, with multiple groups reporting structural and functional abnormalities in cells and tissues of Pkd1 mutants [47, 42]. We and others have also described direct physical and functional links between PC1 and mitochondria[6, 7, 42].…”
Section: Discussionmentioning
confidence: 99%